Perbedaan Pertumbuhan Bayi Usia 0-6 Bulan yang Mendapat Asi Ekslusif dan Asi Non Ekslusif di UPTD Puskesmas Langsa Timur - Surnimawati Surnimawati; Rotua Lenawati Tindaon; Teti Marlina; Tasya Tasya; Suryati Suryati; Tia Aulia (Malahayati Nursing Journal, 2023)
ABSTRACT Based on UNICEF data in 2020, three regions have a very high prevalence of growth disorders, with around a third of children affected. The aim of the study was to determine the differences in the growth of infants aged 0-6 months who were exclusively breastfed and non-exclusively breastfed. What will be carried out by the East Langsa Health Center UPTD will be held on April 26-November 2022. The entire population is taken as a sample, namely 30 people. The design of this study is descriptive analytic, with a cross sectional approach using data analysis using the Chi-Square test method to test hypotheses with the help of SPSS. Based on the calculation results of the Chi-Square Statistical Test method, a p-value of 0.042 ± 0.05 was obtained, meaning that Ho was accepted and Ha was rejected so that it could be concluded that there were differences in the growth of infants aged 0-6 months who received exclusive breastfeeding with non-exclusive breastfeeding. The results of the statistical test also obtained an OR value of 7.857, meaning that babies who were not given exclusive breastfeeding had an 8 times greater chance of experiencing poor growth than babies who were given exclusive breastfeeding Keywords: Infant Growth, Exclusive Breastfeeding, Non-Exclusive Breastfeeding  ABSTRAK Berdasarkan data UNICEF pada tahun 2020 tiga wilayah memiliki pravalensi penyimpangan pertumbuhan yang sangat tinggi, dengan sekitar sepertiga anak terkena dampaknya. Tujuan penelitian mengetahui perbedaan pertumbuhan bayi usia 0-6 bulan yang mendapatkan ASI ekslusif dengan ASI non ekslusif. Yang akan dilaksanakan UPTD Puskesmas Langsa Timur, diadakan pada 26 April-November 2022. Semua populasi dijadikan sampel yaitu 30 orang. Desain penelitian ini adalah deskriptif anaSlitik, dengan metode pendekatan cross sectional menggunakan analisa data metodsse Chi-Square test untuk menguji hipotesa dengan bantuan SPSS. Berdasarkan hasil perhitungan metode Uji statistic Chi- Square, diperoleh nilai p-value sebesar 0,042 0,05 artinya Ho diterima dan Ha ditolak sehingga dapat disimpulkan bahwa terdapat perbedaan pertumbuhan bayi usia 0-6 bulan yang mendapatkan ASI eksklusif dengan ASI non eksklusif. Hasil Uji statistik juga memperoleh nilai OR 7,857 artinya bayi yang tidak diberikan ASI Eksklusif memiliki peluang 8 kali lebih besar mengalami pertumbuhan yang tidak baik dari pada bayi yang diberikan ASI Eksklusif.kata kunci: Pertumbuhan Bayi, ASI Ekslusif, ASI non Ekslusif